On simple circular sets of absolute convergence for branched continued fractions of the special form - Antonova, T.M. (Carpathian Mathematical Publications, 2012)
The radii of the circles with center in origin of coordinates that are simple sets of absolute convergence for branched continued fractions of the special form have been investigated.